(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. As a result of active hostilities during the Russian-Ukrainian war, the territory of Ukraine is polluted with a huge amount of toxic metals. Therefore, the problem of cleaning them, in particular water bodies, will be of critical importance for the preservation of ecosystems and the national security of our country for a long time to come. Adsorption is one of the most economically attractive and environmentally friendly ways to remove various pollutants from wastewater, and polymer-inorganic adsorbents are widely used in the processes of wastewater purification from dyes and toxic metal ions. In order to increase their effectiveness in relation to the excess amount of toxic metal ions on the surface of porous inorganic matrices, it is advisable to fix polymers that have in their composition groups that are active in complex formation processes as ligands. This work is devoted to the synthesis of a polymer-inorganic composite material based on silica gel with an adsorbed copolymer of 8-methacryloxyquinoline-5-sulfonic acid with methyl methacrylate, to the study of its physicochemical and sorption properties with respect to Cu(II), Cd(II) and Pb(II) ions. Methods. The fact of copolymer immobilization on the saponite surface was confirmed by comparative analysis of IR spectra and thermograms of the synthesized composite and the original silica gel. Based on the results of thermogravimetric analysis, the stages of thermal destruction of the fixed copolymer were established and the mass fraction of the immobilized copolymer in the synthesized composite was calculated. Using thermogravimetric analysis combined with IR spectroscopy, assumptions were made about the composition of the thermal degradation products of the adsorbed copolymer. Changes in the parameters of the silica gel surface after modification with the selected copolymer were determined using the low-temperature nitrogen adsorption-desorption method. The geometric shape of the location of the copolymer on the surface of silica gel was investigated using scanning electron microscopy. The study of the sorption activity of the synthesized composite with respect to Cu(II), Pb(II), and Cd(II) ions was carried out in the static mode of sorption from nitrate solutions without the addition of buffer solutions. Results. According to the results of thermogravimetric analysis, there was the mass fraction of the immobilized copolymer in the synthesized composite was calculated, which is 20.0±0.5 wt.%. Based on the analysis of scanning electron microscopy photographs of the surface of the synthesized composite, it can be stated that the immobilized copolymer covers most of the silica gel surface with a thin film. It was established that the sorption capacity of the synthesized composite increases by 3.8 times for Cu(II) ions, more than 3 times for Cd(II) ions, and almost ten times for Pb(II) ions compared to the original silica gel. Conclusions. As a result of adsorption of the previously synthesized copolymer of 8-methacryloxyquinoline-5-sulfonic acid with methyl methacrylate on the surface of mesoporous silica gel, a new polymer-inorganic composite material was obtained. Changes in the values ​​of specific surface area, average diameter and pore volume, obtained by computer processing of low-temperature nitrogen adsorption-desorption isotherm data by various methods, indicate that the modification of the silica gel surface with this copolymer does not affect its surface structure, but only reduces its porosity. It was found that the replacement of nitro and azo groups in the composition of the adsorbed copolymer with sulfo groups leads to an improvement in the sorption properties for Cd(II) ions, but to a deterioration in relation to Cu(II) ions.